A Case Study of Algorithms for Morphosyntactic Tagging of Polish Language - Kuta, Marcin; Chrzaszcz, Paweł; Kitowski, Jacek (Computing and Informatics, 2012)
The paper presents an evaluation of several part-of-speech taggers, representing main tagging algorithms, applied to corpus of frequency dictionary of the contemporary Polish language. We report our results considering two tagging schemes: IPI PAN positional tagset and its simplified version. Tagging accuracy is calculated for different training sets and takes into account many subcategories (accuracy on known and unknown tokens, word segments, sentences etc.) The comparison of results with other inflecting and analytic languages is done. Performance aspects (time demands) of used tagging tools are also discussed.